Pengembangan E-Modul Berbasis Hypercontent Pada Mata Pelajaran Bimbingan Ti&K Kelas IX Smp - Widya Aisyah At Thahirah; Syafril Syafril (Publikasi Indonesia, 2022)
The development of hypercontent-based e-modules was carried out as an effort to solve problems experienced by students where when students ask the teacher about material that is not understood, the teacher is less than optimal in providing answers for students, because many students ask. This research aims to produce e-module products in IT&K Guidance subjects in grade IX SMP and determine the validity and practicality of the e-module products developed so that they are valid and feasible to use. This type of research is development research known as Research and Development (R&D), using the 4D development model. The development procedure in this study consists of: (1) Define, (2) Design, (3) Develop, (4) Dessiminate. The validity test was carried out by 3 validators, namely 2 media expert validators and 1 material expert validator. The practicality test was carried out on 30 respondents of class IX students at SMP Negeri 4 Bukittinggi. Based on the results of the feasibility assessment from the media expert, it is categorized as